Gómemez Bravo, Gutmaro y Martín Nájera, Aurelio (coords.), A vida o muerte. Persecución a los republicanos españoles, Madrid, Fondo de Cultura Económica/Cátedra del Exilio, 2018, 285 págs., ISBN: 978-84-375-0797-2 - Casanellas, Pau (2020)
UID/HIS/04209/2019